2014
DOI: 10.1108/whatt-01-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the future of housekeeping operations in Dubai’s five-star hotel industry – room for innovation?

Abstract: Purpose – The purpose of this paper is to evaluate the need for innovation as a means of competitive advantage in the housekeeping (HK) department of five-star hotels in Dubai and consider how the nature of the industry in the region provides particular challenges. Design/methodology/approach – An initial White Paper produced by Amadeus served as the stimulus to conduct a preliminary literature review of innovation in the field of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…All the properties had some form of a vision or mission statement declaring expectations, intentions, promises and guarantees affecting both the employees and the guests, and all the participant groups acknowledged the existence of both official and unofficial versions of these. An exploratory study conducted by Anthonisz (2014) revealed that the terms “innovation” and “creativity” appear regularly, or are embedded, in the company values and philosophies of several five-star hotels in Dubai. Likewise, in New Zealand, lodge guests talked about the general manager or other managers having an innovative and creative input into the overall vision of how the lodges are run, and that the vision came from owner(s) and was implemented by the managers and employees in the lodges.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…All the properties had some form of a vision or mission statement declaring expectations, intentions, promises and guarantees affecting both the employees and the guests, and all the participant groups acknowledged the existence of both official and unofficial versions of these. An exploratory study conducted by Anthonisz (2014) revealed that the terms “innovation” and “creativity” appear regularly, or are embedded, in the company values and philosophies of several five-star hotels in Dubai. Likewise, in New Zealand, lodge guests talked about the general manager or other managers having an innovative and creative input into the overall vision of how the lodges are run, and that the vision came from owner(s) and was implemented by the managers and employees in the lodges.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Hotels may use innovative technology in their operations to improve customer service and satisfaction. Innovation in hotels provides a sustainable competitive advantage (Anthonisz, 2014) by introducing new aspects that will add value (o’sullivan and dooley, 2009; Jayawardena et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many authors agreed that innovation leads to a competitive advantage and consequently of performance and success either in manufacturing (Anderson et al, 2014;Omerzel, 2016) or in the service context (Orfila-Sintes et al, 2005;Hjalager, 2010;Campo et al, 2014;Pikkemaat and Zehrer, 2016) . Hotels could be considered innovative once their features has been involved new development of idea creation, organizational learning and performing or leading change which might happens in one of four dimensions as reported by Anthonisz (2014): first, the product innovation which has changes in the hotel products or the offered services to the target customer; second, process innovation that has changes in the way in which products or services are created and delivered; third, position innovation which means variations in the context in which products or services are introduced; forth, paradigm innovation which has changes in the underlying mental models which structure the purpose of any organization. This previous literature leaded the researcher to the first hypothesis which is: Hypothesis 1: Perceived innovation is a multidimensional concept.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This previous literature leaded the researcher to the first hypothesis which is: Hypothesis 1: Perceived innovation is a multidimensional concept. The main problem of Innovation as reported by Anthonisz (2014) in the hotel industry has frequently been criticized for its absence of innovation. Artič (2013) indicated that innovation is predictable if an organization needs to continue in the market, and nevertheless the hospitality context still seems to be lagging behind, mostly in relation to more inclusive and radical innovations.…”
Section: Literature Reviewmentioning
confidence: 99%